The impact of optimal medical therapy on patients with recurrent acute myocardial infarction: Subanalysis from the BleeMACS study. (1st November 2020) - Zhang, Dongfeng; Song, Xiantao; Raposeiras-Roubín, Sergio; Abu-Assi, Emad; Henriques, Jose Paulo Simao; D'Ascenzo, Fabrizio; Saucedo, Jorge; González-Juanatey, José Ramón; Wilton, Stephen B.; Kikkert, Wouter J.; Nuñez-Gil, Iván; Ariza-Sole, Albert; et al.
Abstract: Background: Acute myocardial infarction (AMI) recurrence is still high despite great progress in secondary prevention. Patients with recurrent AMI suffer worse prognosis compared to those with first AMI. The objective was to evaluate the effect of optimal medical therapy (OMT) on these patients with recurrent AMI. Methods and results: Sub-analysis was performed including 13, 343 patients with AMI from the international multicenter Bleeding complications in a Multicenter registry of patients discharged with diagnosis of Acute Coronary Syndrome (BleeMACS) registry. OMT was defined as the combination of aspirin, any P2Y12 inhibitor, statin, angiotensin converting enzyme inhibitor/angiotensin receptor blocker, and beta-blocker. Among 1285 patients with prior AMI, 56.8% received OMT prescription. Patients receiving OMT suffered from less congestive heart failure, peripheral artery disease, malignancy, and bleeding history. Kaplan-Meier survival estimates revealed that OMT was strongly related to decreased in all-cause death (4.2% vs. 10.1%, p  < .001) and the composite endpoint of death/re-AMI (11.1% vs. 16.9%, p  = .005) at 1-year follow-up. OMT was the independent protect factor of primary endpoint even after adjusting for multiple possible confounders (HR, 0.46; 95% CI, 0.27–0.78; p  = .004). However, no significant difference was observed regarding re-AMI between OMT and non-OMT groups. OMT also reduced all-cause death in patients with recurrent AMI after propensity score matching. Conclusions: The prescription of OMT was seriously insufficient in patients with recurrent AMI, especially high-risk patients, even though OMT was associated with improved prognosis. Further improvements in pharmacological therapy are needed to reduce subsequent recurrent events. Highlights: Recurrent acute myocardial infarction (AMI) is common in clinical practice. The fundamental pharmaceutical therapy has not been well explored in this patient population. This is the first study to evaluate optimal medical therapy (OMT) in recurrent AMI. This study revealed that efforts should be made to prevent continuing recurrent events.